Analisis Perubahan Budaya Lingkungan Sekolah di KB TA Al-Falach - Anggung Dhanar Siniwoko; Shobihatul Fitroh Noviyanti; Moh. Azidan Alfatukhi; Izza Ummi Maghfiroh; Ulya Maulidiyah (Al-Kindi, 2026)
This study aims to identify the types of changes in school environmental culture, analyze the factors influencing these changes, examine the responses of school members, and formulate adaptation and evaluation strategies at KB TA Al-Falach. The findings indicate that the cultural changes include improvements in discipline, environmental cleanliness, and enhanced collaboration among school members. The factors influencing these changes include leadership, communication, and active participation from teachers and educational staff. The responses of school members are generally positive, although there are some challenges in the adaptation process. Adaptation strategies are implemented through habituation, role modeling, and strengthening communication. Evaluation is conducted periodically to ensure the sustainability of the implemented cultural changes. Therefore, this study emphasizes the importance of effective leadership in managing sustainable changes in school environmental culture.